1996
DOI: 10.1016/s0741-5214(96)70025-3
|View full text |Cite
|
Sign up to set email alerts
|

Variation in measurement of ankle-brachial pressure index in routine clinical practice

Abstract: ABPI is routinely used as an objective measure of peripheral vascular disease. The variation observed in this study is comparable with values obtained in reproducibility studies and is greater than that accepted in clinical practice. The difference between an ABPI measurement and the actual ABPI and the difference between repeat single measurements are not the same and should be distinguished. Vascular laboratories should determine the accuracy of ABPI measurement on a local basis to guarantee and maintain qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 11 publications
3
30
0
Order By: Relevance
“…In fact, the difference between the 2 measures was similar to that seen when obtaining repeat ambulatory blood pressure 10 or performing the ABI. 11 Not surprisingly, Doppler ultrasound determination of the ABI and oscillometric-based ABI were quite similar, showing a strong association between the 2 methods. Other studies have evaluated oscillometry in the determination of the ABI.…”
Section: Discussionmentioning
confidence: 86%
“…In fact, the difference between the 2 measures was similar to that seen when obtaining repeat ambulatory blood pressure 10 or performing the ABI. 11 Not surprisingly, Doppler ultrasound determination of the ABI and oscillometric-based ABI were quite similar, showing a strong association between the 2 methods. Other studies have evaluated oscillometry in the determination of the ABI.…”
Section: Discussionmentioning
confidence: 86%
“…Second, there is no ABI cutpoint that is universally accepted as being the best predictor of cardiovascular events, although for screening purposes, it may be hypothesized that an ABI Յ0.9 is likely to be more sensitive in identifying asymptomatic atherosclerosis than a lower cutpoint. Finally, although change in ABI has been related to worsening peripheral arterial disease 7 or outcome after vascular operation, 8 its predictive value for subsequent vascular events has not been investigated in any detail.…”
Section: Discussionmentioning
confidence: 99%
“…Although quick and easy to perform with a high patient acceptability, the ABI was originally used to identify lower-limb atherosclerosis. How-ever, it has subsequently been shown to be an accurate 7,8 and reliable 9 marker of generalized atherosclerosis. Cohort studies with between 5 and 10 years of follow-up have shown that people with a low ABI have an increased risk of both cardiovascular morbidity 10 and mortality.…”
mentioning
confidence: 99%
“…7,10 Information has been published about the variability of ABI measurements. [10][11][12][13][14][15][16][17][18][19][20][21][22] In general, in these studies, the variability is expressed as a percentage of the average observed ABI values ranging from 8% to 16%, whereas in absolute values the standard deviation of the difference of repeated ABI measurements was between ±0.10 and ±0. 15.…”
Section: Introductionmentioning
confidence: 99%